2015
DOI: 10.1038/nrurol.2015.192
|View full text |Cite
|
Sign up to set email alerts
|

Urinary flow rate after TIP urethroplasty for hypospadias

Abstract: Refers to Andersson, M. et al. Normalized urinary flow at puberty after tubularized incised plate (TIP) urethroplasty of hypospadias in childhood. J. Urol. http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Authors have reported that patients with hypospadias show abnormal (though subclinical) flow patterns postoperatively [ 4 17 18 ]. Some authors have also noted a frail correlation between flow and clinical symptoms [ 3 ]. Because of this, a single uroflowmetry test or single voiding video test cannot represent the long-term result of hypospadias surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors have reported that patients with hypospadias show abnormal (though subclinical) flow patterns postoperatively [ 4 17 18 ]. Some authors have also noted a frail correlation between flow and clinical symptoms [ 3 ]. Because of this, a single uroflowmetry test or single voiding video test cannot represent the long-term result of hypospadias surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Urethral stricture is the second most common complication of hypospadias surgery [ 1 2 ]. In general, assessments of functional outcome are performed on the basis of patients' complaints about stream of micturition and the results of uroflowmetry tests after urethroplasty [ 3 ]. The measurement of urinary flow is a simple and noninvasive procedure that provides an objective evaluation of the urinary stream, and it has been used for a long time in urologic practice [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%